Evaluation of Celest Top® 312.5 FS (fludioxonil 25g/L; difenoconazole 25g/L; thiamethoxam 262g/L) to control insect pests and seedling diseases on wheat at River Nile and Kassala States, Sudan (Journal of Basic and Applied Research in Biomedicine, 2022)
The experiments were conducted at Hudiaba research station farm (River Nile State) and New halfa Research Station (Kassala State) for two consecutive seasons 2014/015 and 2015/016, to evaluate the effectiveness of Celest Top 312.5 FS (flowable solution) as seed dressing to control insect pests and seedling diseases of wheat. Celest Top 312.5 FS was used at the rates of 1.25ml/kg seed, 1ml/kg seed and 0.75 ml/kg seed with its respective (standard) check 1.5g/kg Raxil2% WS (tebuconazole) + 0.5g/kg Gaucho70% WS (imiddacloprid) and untreated control. In contrast, Celest Top 312.5 FS at the rates of 1ml/kg and 1.25ml/kg seed significantly (P≤ 0.01) reduced green bug and termite infestation and seedling diseases of wheat and increased wheat grain yield compared to the untreated and standard. In vitro evaluation of Celest Top 312.5 FS against Pythium spp. revealed that the pesticide containing fungicidal components significantly inhibited the mycelia growth of test pathogen. Results of residue analysis showed that no detectable levels of Celest Top 312.5 FS were found in all samples of wheat collected at harvest.